Pengaruh Pengembangan Sumber Daya Manusia dan Budaya Organisasi Terhadap Human Capital Strategy pada Start up Sektor Bisnis Education Technology di Indonesia - Mugi Puspita; Rian Japesa (LPPM UNIBI, 2024)
This research aims to examine the influence of human resource development and organizational culture on human capital strategy in education technology start-ups in Indonesia. Data research techniques use descriptive and verification methods with the Smart-PLS application. This research is included in non-experimental research (survey), where survey research conducts a study of the population by selecting samples from that population. The research sample consisted of 53 start-up education technology companies in Indonesia. The research results show that HR development has an influence on human capital strategy. Organizational culture has no influence on human capital strategy.